A Comprehensive approach to Daily Routine with Respect to the Concept of Dincharya - Kaur, Paramjeet; Shukla, Amit Kumar; Mishra, Archna (International Research Journal of Ayurveda & Yoga, 2024)
Lifestyle simply means “the way in which person lives”. The daily activities of person since he wakes up to fall asleep are included in this. It includes dietary habit, the nature of his work, exercise, hobbies and leisure time activities. Health is a state of complete physical, mental and social well-being and not merely the absence of disease or infirmity. No such concept appears to be present in contemporary medical practices although a lot of importance has been given to dietary regulations and exercise in prevention and management of non-communicable diseases such as ischemic heart disease and diabetes mellitus. The present study had been undertaken to collect modern scientific evidences in support of Dinacharya (daily regimen) mentioned in ancient Ayurvedic texts and its role in preventing non communicable diseases.